Suprageneric taxa derived from Amblycoryphini sensu lato (Orthoptera: Tettigonioidea: Phaneropteridae: Phaneropterinae) - Cadena-Castañeda, Oscar J. (Zootaxa, 2015)
Based on the current description of the tribe Amblycoryphini some related genera have been excluded. These genera comprise two new tribes (Vossiini n. trib. and Plangiopsiini n. trib.) and a new generic group (Plangiae n. group). The main differences between the taxa described and the tribe Amblycoryphini are discussed, to understand the new proposed classification. Plangiopsis aedeps is placed in the genus Plangiola. This paper contributes to the knowledge of the tettigonid fauna from Africa and understanding of the taxonomy of neotropical Phaneropterinae.